Dapagliflozin: a new adjunct in the treatment of Type 2 diabetes mellitus - Sachdeva, Mamta; Dhingra, Sameer; Parle, Milind (International Journal of Basic & Clinical Pharmacology, 2017)
Diabetes mellitus (DM) Type 2 is a metabolic disorder that is characterized by high blood glucose in the context of insulin resistance and relative insulin deficiency. The classic symptoms are excess thirst, frequent urination, and constant hunger. Management of Type 2 diabetes focuses on lifestyle interventions, lowering other cardiovascular risk factors, and maintaining blood glucose levels in the normal range. There are several classes of anti-diabetic medications available and these include sulfonylureas, nonsulfonylurea secretagogues, alpha glucosidase inhibitors, thiazolidinediones, glucagon-like peptide-1 analog, and dipeptidyl peptidase-4 inhibitors. Recently, dapagliflozin (Farxiga™), a sodium-glucose cotransporter 2 inhibitor has been approved by Food and Drug Administration as an adjunct to diet and exercises to improve glycemic control in adults with Type 2 DM.